2020
DOI: 10.3390/su12051975
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Research Framework of Future Sustainable Urban Freight Transport for Smart Cities

Abstract: This paper aims to construct a theoretical research framework for sustainable urban freight transport (SUFT) from the perspectives of future urban development and distribution innovations, and appropriate research methods are discussed, as well. Urban freight transport plays a critical role in the promotion of sustainable and livable cities. According to the literature review, considerable research on SUFT has focused on resolving some specific problems with a short-term perspective. The existence of an urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…Freight transport in cities is seen as a source of pollution, noise, traffic congestion and have a negative impact on safety [12,13] and, despite the civilizational need to move cargo by road, road transport in general is viewed in a negative way [14]. The volume of urban freight transport is constantly growing, causing demand for vehicle movement and service space, congestion, emission of GHGs (greenhouse gases) and noise, and accidents [15,16]. However, city authorities are constantly seeking ways of improving safety of traffic in cities, mostly by developing road infrastructure, resulting in less congestion and better accommodation of traffic flows [17].…”
Section: Literature Overviewmentioning
confidence: 99%
“…Freight transport in cities is seen as a source of pollution, noise, traffic congestion and have a negative impact on safety [12,13] and, despite the civilizational need to move cargo by road, road transport in general is viewed in a negative way [14]. The volume of urban freight transport is constantly growing, causing demand for vehicle movement and service space, congestion, emission of GHGs (greenhouse gases) and noise, and accidents [15,16]. However, city authorities are constantly seeking ways of improving safety of traffic in cities, mostly by developing road infrastructure, resulting in less congestion and better accommodation of traffic flows [17].…”
Section: Literature Overviewmentioning
confidence: 99%
“…1) Reducing urban logistics inefficiencies in order to achieve a reduction in costs and externalities (1 st principle); 2) Resolving the effects of customer's poor planning (2 nd principle), and 3) Using the intermodal transport success factors (3 rd principle) Based on the analysis of the scientific literature, a gap has been identified in the existence of an urban logistics model that uses a combination of the principles mentioned here. It can be concluded that there is a necessity for a model that promotes the business aspects of urban logistics and intermodal transport principles, as a future research in the urban freight system [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The coexistence of inefficiency in urban logistics and waste of resources, due to the nature of business, is a sign of a market inconsistencies. There is lack of long term planning of sustainable urban freight transport [9] with the last 25 years of research in sustainable urban logistics being dominated by technical problems [10]. Urban logistics requires new sustainable solutions and models reduction, resolving the effects of customer's poor planning, and using the intermodal transport success factors.…”
Section: Introductionmentioning
confidence: 99%
“…We narrow down our scope to city logistics, which by itself is complex and can be improved on many dimensions [13]. Literature sees crowdshipping as the more sustainable solution to city logistics [14], because of its potential in terms of economic and environmental benefits [15].…”
Section: Introductionmentioning
confidence: 99%